2013
DOI: 10.1038/emm.2013.116
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin contracts the rat mesenteric artery by inhibiting 4-aminopyridine-sensitive Kv channels via the 5-HT2A receptor and Src tyrosine kinase

Abstract: Serotonin (5-hydroxytryptamine (5-HT)) is a neurotransmitter that regulates a variety of functions in the nervous, gastrointestinal and cardiovascular systems. Despite such importance, 5-HT signaling pathways are not entirely clear. We demonstrated previously that 4-aminopyridine (4-AP)-sensitive voltage-gated K+ (Kv) channels determine the resting membrane potential of arterial smooth muscle cells and that the Kv channels are inhibited by 5-HT, which depolarizes the membranes. Therefore, we hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 43 publications
(65 reference statements)
3
46
0
Order By: Relevance
“…Increased tyrosine phosphorylation is closely associated with VSM contraction. Src tyrosine kinase was reported to be a critical regulator of rat arterial vasocontraction [11,12]. The western blotting results in this study also showed that 445 nm laser irradiation induced phosphorylation of tyrosine residues in proteins, including those with the molecular weight of Src tyrosine kinase ( Fig.…”
Section: Irradiation With the 445 Nm Laser Activated Ptks Of Vsmsupporting
confidence: 56%
See 2 more Smart Citations
“…Increased tyrosine phosphorylation is closely associated with VSM contraction. Src tyrosine kinase was reported to be a critical regulator of rat arterial vasocontraction [11,12]. The western blotting results in this study also showed that 445 nm laser irradiation induced phosphorylation of tyrosine residues in proteins, including those with the molecular weight of Src tyrosine kinase ( Fig.…”
Section: Irradiation With the 445 Nm Laser Activated Ptks Of Vsmsupporting
confidence: 56%
“…To assess the contribution of VLCC-dependent and -independent regulation of 445 nm laser-induced changes in the contraction of VSM, 5-HT (instead of 35 mM KCl) was used for precontraction in some experiments. The 5-HT-induced VSM contraction was reportedly Src tyrosine kinase-dependent [11] and was composed of ~70% VLCC-dependent and ~30% VLCC-independent contractions [12,14]. Irradiation with the 445 nm laser initially relaxed endothelium-denuded aortic rings pre-contracted with 5-HT (10 μM), but was followed by contraction (Fig.…”
Section: Effects Of Laser Irradiation On Vsm Without Endotheliummentioning
confidence: 99%
See 1 more Smart Citation
“…However, a nonspecific effect of 4-aminopyridine can be excluded, at least in the bovine retinal arteries, as previously documented that the relaxations to the directly acting vasodilator, sodium nitroprusside (SNP) were unaffected by 4-aminopyridine in this artery (Boussery et al, 2005). In addition, TEA does not always display identical properties with 4-aminopyridine in mediating the vasorelaxation (Novakovic et al, 2006) and regulating the vascular tone (Sung et al, 2013). Thus, this discrepancy is more likely to be related to the existance of different types of K v channel currents and the diverse sensitivities of 4-aminopyridine and TEA towards these currents.…”
Section: Discussionmentioning
confidence: 83%
“…34) This study showed that K V 2.1 inhibition-induced contractile responses were enhanced in the RAs of Dahl-HS. On the other hand, Song et al have shown that K V 2.1 activity is enhanced by Src-mediated phosphorylation in neurons.…”
Section: Discussionmentioning
confidence: 87%